Implementation of The Demonstration Method at Madrasatul Qur'an in Ngalah Islamic Boarding School - Nizar, Ahmad; Jamhuri, M. (At- Ta'lim : Jurnal Pendidikan, 2025)
This study aims to explore the implementation of the teaching aids method in learning the Qur'an at Madrasatul Qur'an Ngalah Islamic Boarding School, Pasuruan. The approach used is qualitative with the type of case study. Data collection techniques include participatory observation, in-depth interviews, and documentation, with research subjects consisting of teachers, students, and MQ managers. The results showed that the teaching method was proven to improve students' understanding of Al-Qur'an material, strengthen memorization, and create an active and fun learning atmosphere. However, obstacles such as limited tools, lack of teacher training, and lack of assistance from the central board are still the main obstacles in optimizing this method. This study recommends the need for continuous training for teachers, the development of contextual teaching aids, and managerial support from the institution to improve the quality of Qur'an learning in the pesantren environment.